Percepción del estudiantado sobre la ética en la investigación de la lingüística aplicada en una universidad pública costarricense - Charpentier-Jiménez, William (Universidad de Costa Rica, 2023)
This article examines students’ perceptions of ethics and ethical training in research on second language acquisition. The role of ethics in applied linguistics and research has received little attention, despite its relevance. This study, which was conducted from May to June 2022, involved 26 TESOL students enrolled in a Licenciatura program at a Costa Rican public university. It used a quantitative, direct needs assessment design. The researcher collected data through a survey designed to elicit students’ opinions on this issue. Quantitative data were analyzed using descriptive statistics. Data analyses indicate that: 1) students tend to reject unethical behaviors in research (68.75%); 2) some behaviors seem more permissible than others; 3) students consider ethics an essential component of research (x̅ = 4.6, SD = 0.57, Mod = 5); and 4) the Licenciatura program does not incorporate a systematic approach to ethical training in SLA research (X̄ = 9.33; SD = 8.08. Consistent with the reviewed literature, these findings demonstrate the lack of ethical training in language teaching programs and second language research. Furthermore, the analysis suggests that direct instruction may broaden students’ understanding of ethical issues when conducting research. Finally, these findings suggest that students would greatly benefit from a more structured curriculum that considers the ethical component of research.